Peace News and Radical Disability Writing in 1970s Britain: Perceptions of Welfare and the Welfare State - Hampton, Jameel (Disability Studies Quarterly, 2020)
The 1970s were an important decade for disability policy in Britain. The 1970 Chronically Sick and Disabled Persons Act promised services for all disabled people and a series of cash benefits appeared to comprise a national disability income. By the 1980s, however, these measures had failed, and some disabled people had taken radical stances against the perceived failures of capitalism. This article shows that radical views amongst disabled people began earlier and were more common than has been assumed. It examines Peace News, a prominent activist publication, as evidence of this phenomenon. Disabled people in the 1970s became radicalised in response to traditional failures of British welfare and recent failures of the welfare state. They self-identified as a minority group—alongside homosexuals and ethnic minorities—and fought against discrimination. Unlike major disability organisations in the 1970s, disabled people had a militant approach to improving their welfare and their position in the welfare state.